The Cost of Political Connections - Bertrand, Marianne; Kramarz, Francis; Schoar, Antoinette; Thesmar, David (Review of Finance, 2018)
Using plant-level data from France, we document a potential cost of political connections for firms that is not offset by other benefits. Politically connected CEOs alter corporate employment decisions to help (regional) politicians in their re-election efforts by having higher job and plant creation rates, and lower rates of destruction in election years, especially in politically contested areas. There is little evidence that connected firms benefit from preferential access to government resources, such as subsidies or tax exemptions. Connected firms are less profitable in the cross-section and also experience a drop in profitability when a connected CEO comes to power.